Platelet Counts and Patent Ductus Arteriosus in Preterm Infants: An Updated Systematic Review and Meta-Analysis - González-Luis, Gema; Ghirardello, Stefano; Bas-Suárez, Pilar; Cavallaro, Giacomo; Mosca, Fabio; Clyman, Ronald I; Villamor, Eduardo (Frontiers in Pediatrics, 2021)
Background: A meta-analysis published in 2015 showed a significant association between low platelet counts in the first day(s) of life and risk of patent ductus arteriosus (PDA). The meta-analysis pooled data from 11 studies cohorts (3,479 preterm infants). Objective: To update the meta-analysis by adding new studies on the topic and including other platelet parameters different from platelet counts. Methods: PubMed/Medline and Embase databases were searched. Random-effects risk ratios (RR) and differences in means (DM) and 95% confidence intervals (CI) were calculated. Results: We included 31 studies (7,638 infants). Meta-analysis showed that the risk of developing any PDA was significantly associated with platelet counts<150 × 109/L (11 studies, RR 1.58, 95% CI 1.28 to 1.95), and <100 x 109/L (7 studies, RR 1.61, 95% CI 1.14 to 2.28), but not <50 x 109/L (4 studies, RR 1.34, 95% CI 0.77 to 2.32). Risk of developing hemodynamically significant PDA (hsPDA) was significantly associated with platelet counts<150 x 109/L (12 studies, RR 1.33, 95% CI 1.09 to 1.63), and <100 x 109/L (7 studies, RR 1.39, 95% CI 1.06 to 1.82), but not <50 x 109/L (6 studies, RR 1.24, 95% CI 0.86 to 1.79). Infants with hsPDA had significantly lower mean platelet counts (19 studies, DM 22.0 x 109, 95% CI 14.9 to 29.1) and platelet mass (11 studies, DM 214.4, 95% CI 131.2 to 297.5) and significantly higher platelet distribution width (PDW, 9 studies, DM −0.53, 95% CI −1.01 to −0.05) than infants without hsPDA. Meta-analysis could not demonstrate significant differences in mean platelet volume (MPV). Conclusion: Compared to the previous analysis, this updated meta-analysis included 21 additional studies that provide stronger evidence of the association between low platelet counts and PDA/hsPDA. Other platelet parameters such as platelet mass and PDW are also associated with hsPDA risk. However, the low number of platelets may be an epiphenomenon associated with the maturity and clinical stability of preterm infants rather than a contributing factor in the pathogenesis of PDA.